Biological response of rats to resistant starch - Walter, Melissa; da Silva, Leila P.; Perdomo, Daiana M. X. (Revista do Instituto Adolfo Lutz, 2005)
Several investigations have been done on resistant starch (RS) due to its beneficial effects, such as reduction of dietary energy, increased fecal production and growth of beneficial microorganisms in intestinal tract, among others. The present study aimed at evaluating the influence of RS on some biological response parameters. Male Wistar rats (97.1±5.3g) were fed diets supplemented with 0, 3, 9 and 18% of RS. Animals were submitted to an adaptation period of five days. During the experimental period (15 days), data and samples were obtained to assess the following parameters: feed intake, body weight gain, apparent dry matter digestibility, apparent starch digestibility, wet and dry fecal production, fecal water content, pH and nitrogen. Addition of RS to the diets did not influence the feed intake, but it significantly reduced the animals body weight. Wet and dry fecal productions were significantly higher at adding 9 and 18% of RS. The consumption of RS also significantly increased the water content and nitrogen excretion in feces, and decreased the fecal pH. The effects observed in the present study might essentially resulted from reduced apparent starch digestibility,and from its fermentation by intestinal microflora, demonstrating the beneficial effects of RS on health maintenance.